Sedimentology and Geochemistry of Selected Glacial Sediments from Central Minnesota as a Method for Correlation and Provenance Studies of Glacial Stratigraphic Units - Gowan, Angela Suzanne (1993)
A Thesis submitted to the faculty of the Graduate School of the University of Minnesota by Angela Suzanne Gowan in partial fulfillment of the requirements for the degree of Master of Science, 1993. The results of this investigation indicate that studies of the glacial stratigraphy and provenance of tills in Minnesota would be best served by using the geochemistry of the silt and clay fractions as the primary tool, regardless of expected local stratigraphy. Additional useful methods, in order of importance, are: rock magnetic properties, sand grain lithology, and grain size analysis. This conclusion was obtained through the use of graphical and multivariate statistical comparisons of grain size, matrix carbonate content, rock magnetic properties, sand grain lithology, and silt and clay fraction geochemistry data from six groups of Minnesota tills of diverse provenance (the northwestern New Ulm, Granite Falls, and Browerville tills, the northeastern Brainerd and Independence (and underlying) tills, and the historically controversial Hewitt till). Only the geochemistry data was able to distinguish between the six till groups, and provide provenance information as well, designating the Hewitt till as of definitely northeastern provenance. Additional statistical analysis of the geochemistry of carbonate pebbles from the till samples was unable to distinguish between carbonates from the Hudson Bay Lowland and the Winnipeg area.